USIA KAWIN PADA UU No. 16 TAHUN 2019 PERUBAHAN ATAS UU No. 1 TAHUN 1974 TENTANG PERNIKAHAN PRESPEKTIF KESEHATAN MENTAL - Muhammad; Suhari (Menara Tebuireng, 2022)
The Act No. 16 of 2019 amending the Law No. 1 of 1974 on Marriage, changed the age limit for marriage specifically for women to 19 years. In this regard, the government is trying to change the social conditions of the society related to the health of children and mothers, early marriages, educational opportunities and prevention of discrimination. Based on this, the author tries to look at the minimum marriage age in the mental health perspective to prepare the spouses physically, mentally and materially. The results show that being mentally and physically healthy and not experiencing disturbances will have a strong influence on individual behavior, relations with family, relationships with others and relations with their surroundings. All such preparations must be accompanied by understanding and good religious practices to realize the purpose of marriage, namely, sakinah, mawaddah and warahmah. Keywords: Age of marriage, law, mental health